2016
DOI: 10.1108/jima-02-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Can halal certification influence logistics performance?

Abstract: Purpose The purpose of this paper is to establish the halal certification–logistics performance relationship by means of developing a theoretical model and to suggest areas for future research undertakings. The relationship between various forms of certification and logistics performance has been reported in many logistics literature. However, there is paucity in research concerning the relationship between halal certification and logistics performance. Design/methodology/approach The literature representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 64 publications
2
80
0
1
Order By: Relevance
“…To support the argument, evidence from past research indicated that firms utilised various types of certification as an instrument to achieve desired business outcomes (Talib et al, 2016b;Fikru, 2014;Kafetzopoulos and Gotzamani, 2014;Sampaio et al, 2009;Chow-Chua et al, 2003;Sum et al, 2001). Likewise, Talib et al (2016b, p. 470) explained that "apart from implementing Halal certification as a tool to gain business legitimacy, industry practitioners use Halal certification as a mechanism to improve organisational performance".…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
“…To support the argument, evidence from past research indicated that firms utilised various types of certification as an instrument to achieve desired business outcomes (Talib et al, 2016b;Fikru, 2014;Kafetzopoulos and Gotzamani, 2014;Sampaio et al, 2009;Chow-Chua et al, 2003;Sum et al, 2001). Likewise, Talib et al (2016b, p. 470) explained that "apart from implementing Halal certification as a tool to gain business legitimacy, industry practitioners use Halal certification as a mechanism to improve organisational performance".…”
Section: Research Framework and Hypothesesmentioning
confidence: 99%
“…"[Halal food certificate] food companies have the potential to improve the productivity and standardizing internal operations." Business performance Increase productivity Standardizing products Ab Talib, Abdul Hamid, and Chin (2016) "[Halal certification] will affect the growth of the consumer's base, increase the numbers of consumers and also increase the revenue of the firms." Based on the mentioned studies, the Halal industry can increase the income and quality of people's life through trade, investment, service provision and employment opportunities.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the procedures and Matrix 3 assisted the processing plant to prioritise and allocate resources accordingly. Ab Talib et al (2016) suggested that proper application of resources could influence halal food production and halal logistics performance. Improving employees' capacity was identified as the top priority in Matrix 3.…”
Section: Discussionmentioning
confidence: 99%